A diary study of work-related reading: Design implications for digital reading devices - Adler, Annette; Gujar, Anuj; Harrison, Beverly L.; O'Hara, Kenton; Sellen, Abigail (Proceedings of CHI '98, ACM, New York, 1998)
In this paper we describe a diary study of how people read in the course of their daily working lives. Fifteen people from a wide variety of professions were asked to log their daily document activity for a period of 5 consecutive working days. Using structured interviews, we analysed their reading activities in detail. We examine the range of reading activities that our subjects carried out, and then present findings relating to both common characteristics and variation across the sample. From these findings, we discuss some implications for the design of digital reading devices. *Authors are listed alphabetically.